Quantification of dengue virus specific T cell responses and correlation with viral load and clinical disease severity in acute dengue infection - Wijeratne, DT; Fernando, S; Gomes, L; Jeewandara, C; Ginneliya, A; Samarasekara, S; Wijewickrama, A; Hardman, CS; Ogg, GS; Malavige, GN (Public Library of Science, 2018)
Background In order to understand the role of dengue virus (DENV) specific T cell responses that associate with protection, we studied their frequency and phenotype in relation to clinical disease severity and resolution of viraemia in a large cohort of patients with varying severity of acute dengue infection. Methodology/Principal findings Using ex vivo IFNγ ELISpot assays we determined the frequency of dengue viral peptide (DENV)-NS3, NS1 and NS5 responsive T cells in 74 adult patients with acute dengue infection and examined the association of responsive T cell frequency with the extent of viraemia and clinical disease severity. We found that total DENV-specific and DENV-NS3-specific T cell responses, were higher in patients with dengue fever (DF), when compared to those with dengue haemorrhagic fever (DHF). In addition, those with DF had significantly higher (p = 0.02) DENV-specific T cell responses on day 4 of infection compared to those who subsequently developed DHF. DENV peptide specific T cell responses inversely correlated with the degree of viraemia, which was most significant for DENV-NS3 specific T cell responses (Spearman’s r = -0.47, p = 0.0003). The frequency of T cell responses to NS1, NS5 and pooled DENV peptides, correlated with the degree of thrombocytopenia but had no association with levels of liver transaminases. In contrast, total DENV-IgG inversely correlated with the degree of thrombocytopenia and levels of liver transaminases. Conclusions/Significance Early appearance of DENV-specific T cell IFNγ responses before the onset of plasma leakage, appears to associate with milder clinical disease and resolution of viraemia, suggesting a protective role in acute dengue infection.